Phenological Patterns and Seasonal Segregation of Coprophilous Beetles (Coleoptera: Scarabaeoidea and Hydrophilidae) on a Cattle Farm in SE-Michigan, United States Throughout the Year - Wassmer, Thomas (Frontiers in Ecology and Evolution, 2020)
The seasonal occurrence of species and timing of key events in their life (phenology) affects the ecology and evolution of every species, population, and species community (SC) on Earth. Shifting phenologies and mismatches between species may affect range limits and lead to extinctions and biodiversity loss, which are especially concerning in ecologically and economically important SCs like coprophilous beetles. This study provides phenological data for many species of coprophilous beetles from the Midwestern region of the US, includes the often-missing winter months, and compares the seasonal and successional differences between the “relocator” and “dweller” guilds. Beetles were sampled biweekly throughout the year from a 3.8 ha Farm in Adrian, SE-Michigan using 15 pitfall traps baited with cow manure. Samples were collected after 48 h and again after 72 h exposure time. Over the entire year, I caught 6069 specimens from 24 species of Scarabaeoidea and 13 species of Hydrophilidae. The ROSARIO null model for continuous temporal data suggested a significant seasonal overlap of the SC (p < 0.0001) and a cluster analysis based on Pianka’s niche overlap index identified five clusters at a minimum overlap of 55 % falling into three major phenological guilds. “Relocators” (6 Scarabaeinae, 2 Aphodiinae species) overlapped on average by 48.4 %, whereas “dwellers” (9 Aphodiinae, 10 Hydrophilidae species) overlapped by 36.0 % (Mann-Whitney test, p = 0.055). Small Hydrophilidae dwellers overlapped by 30.9 % whereas large hydrophilid dwellers overlapped by 96.9 %. Individual phenological patterns were compared to other sites in North America and Europe and predictions about geographical and phenological changes due to the man-made climate crisis and habitat loss and fragmentation are discussed. Differences between the seasonal overlaps of “relocators” and “dwellers” as well as small and large Onthophagus relocators and Hydrophilidae dwellers are suggesting profound ecological differences between the guilds and sub-guilds.